Preoperative Cognitive Stratification of Older Elective Surgical Patients: A Cross-Sectional Study. (July 2016) - Culley, Deborah J.; Flaherty, Devon; Reddy, Srini; Fahey, Margaret C.; Rudolph, James; Huang, Chuan Chin; Liu, Xiaoxia; Xie, Zhongcong; Bader, Angela M.; Hyman, Bradley T.; Blacker, Deborah; Crosby, Gregory
Abstract : BACKGROUND: Preexisting cognitive impairment is emerging as a predictor of poor postoperative outcomes in seniors. We hypothesized that preoperative cognitive screening can be performed in a busy preadmission evaluation center and that cognitive impairment is prevalent in elective geriatric surgical patients. METHODS: We approached 311 patients aged 65 years and older presenting for preoperative evaluation before elective surgery in a prospective, observational, single-center study. Forty-eight patients were ineligible, and 63 declined. The remaining 200 were randomly assigned to the Mini-Cog ( N =100) or Clock-in-the-Box [CIB; N = 100)] test. Study staff administered the test in a quiet room, and 2 investigators scored the tests independently. Probable cognitive impairment was defined as a Mini-Cog ⩽ 2 or a CIB ⩽ 5. RESULTS: The age of consenting patients was 73.7 ± 6.4 (mean ± SD) years. There were no significant differences between patients randomly assigned to the Mini-Cog and CIB test in age, weight, gender, education, ASA physical status, or Charlston Index. Overall, 23% of patients met criteria for probable cognitive impairment, and prevalence was virtually identical regardless of the test used; 22% screened with the Mini-Cog and 23% screened with the CIB scored as having probable cognitive impairment ( P = 1.0 by χ 2 analysis). Both tests had good interrater reliability (Krippendroff α = 0.86 [0.72–0.93] for Mini-Cog and 11 for CIB). CONCLUSIONS: Preoperative cognitive screening is feasible in most geriatric elective surgical patients and reveals a substantial prevalence of probable cognitive impairment in this population. Abstract : Published ahead of print March 29, 2016